When the Center Does Not Hold : Leading in an Age of Polarization - Brubaker, David R.; Haase, Teresa J.; Yoder, Carolyn E.; Brubaker, Everett N. (Book collections on Project MUSE., 2019)
Over the past forty years, congregations, businesses, other organizations, and communities across the United States have become increasingly divided along political and ideological lines. In When the Center Does Not Hold, David R. Brubaker, with contributions by colleagues Everett Brubaker and Carolyn Yoder, offers relevant, practical mentorship on navigating polarized environments. Through easily accessible stories, they provide tools and processes that will equip leaders to both manage themselves and effectively lead others in highly polarized and anxious systems. Coaching includes guidance on key characteristics of effective leadership in times of polarization: managing yourself, building a strong team, clarifying identity and vision, mourning the losses, staying connected, and knowing when it's time to let go (as a leader). With years of combined experience in the fields of conflict transformation and organizational and leadership studies, Brubaker and his colleagues offer hope. Here, readers learn from leaders and communities that continue to renew the covenants that bind them, courageously address deeper needs that drive conflict, and hold on to a moral center while navigating the storms of polarization.